Alleviating Extreme Poverty Through Community Empowerment Programs - Didi, La (Advances In Social Humanities Research, 2024)
Extreme poverty remains a persistent issue in Indonesia, particularly in Central Buton Regency, despite numerous government initiatives. Efforts to alleviate poverty have yet to yield substantial results, with significant disparities between rural and urban areas. This study aims to assess the impact of community empowerment programs on reducing extreme poverty in Central Buton Regency, Indonesia. Using a qualitative descriptive design, data were collected through interviews, observations, and documentation involving individuals living in extreme poverty and government officials managing poverty alleviation programs. The data were analyzed using descriptive statistics and thematic analysis, with findings validated through data source triangulation. The results indicate that community empowerment programs play a crucial role in reducing extreme poverty, though there are discrepancies between expected and actual outcomes. Further research is needed to explore the long-term impact of these programs on poverty reduction in the region.